Le passage du fordisme au néolibéralisme au Canada - Jean-Guy Loranger; Gérard Boismenu (Revue de la Régulation)
A dynamic heterodox model for an open economy is built from the Marxist and Regulationist approaches. Although the Error Correction Model (cointegration analysis) is rarely used by heterodox economists, that method of estimation is used for a long-run period 1947-1999 and for two sub-periods: 1947-75 and 1976-99. The change in the magnitude of parameters validates the importance of structural changes that occurred between the Fordist period and the post-Fordist period, called a neoliberal regime. The main structural changes are the de-linkage of the US dollar from gold, the change of the exchange regime, the end of the cold war, the change of monetary policy, the change of the distribution rate in favour of capital (and financial capital via financial derivatives), the decreasing impact of productivity on real wage and aggregate demand, the increase of the impact of the state on productivity via its expenditures on education, health and other infrastructure expenditures.